The 2000 Presidential election and the foundations of party politics - Johnston, Richard 1948- (Cambridge University Press, 2004)
In the aftermath of the 2000 presidential election, campaigns suddenly seem to matter, as do questions about the electoral process. Professors Johnston, Hagen and Jamieson have examined the US electoral process as an integrated event spanning a full year, drawing upon a data set that is massive in scale and novel in execution: the Annenberg 2000 Election Study. The scale of their fieldwork is such that they have been able to isolate key turning points and that dynamics can be studied within certain segments. The interviews are rich in opinion about policy, perception, information and judgement about candidates, media use and strategy. What is more, the authors have used candidate appearances, news coverage, and campaign advertising to provide the first integrated account of this or any US campaign